Biochemical Composition and Biological Activities Assessment of Periploca laevigata and Thymus algeriensis Leaves Extracts - Gadhoumi, Hamza; Tounsi, Moufida Saidani; Hayouni, El Akrem (Journal of Basic & Applied Sciences, 2020)
The plant traditional medical application indicates great antioxidant and antimicrobial properties. The present study investigated the Biochemical and antimicrobial and antifungal activity of Periploca laevigata and Thymus algeriensis leaves extracts. The biochemical (total phenolic content, total flavonoids, and condensed tannins) and biological activity (antioxidant potentials, and antimicrobial activities) of leaf extractsof Periploca laevigata and Thymus algeriensis were assessed. The results showed that the leaves of the Thymus algeriensis extract has the highest levels of polyphenols, flavonoids, and tannins 120 ± 2.02 mg GAE/g DR, 46 ± 2.5 mg RE/g DR, and 22± 2mg CE/g DR, respectively. The GC-MS analyses showed that the plants haveinteresting volatile compounds. Therefore, leaves of Thymus algeriensis extract possess high anti-oxidant activities (total antioxidant capacity, 2,2-diphenyl-1-picrylhydrazyl and ferric reducing antioxidant power scavenging activities). In addition, this extract exhibited high antifungal and antimicrobial activities, especially toward Gram-positive bacteria. This results highlights ‘importance as dietary sources for natural antioxidants and antimicrobial can be used in traditional medicine and the pharmaceutical industry.